2017
DOI: 10.1021/acs.nanolett.7b03052
|View full text |Cite
|
Sign up to set email alerts
|

Directed Two-Photon Absorption in CdSe Nanoplatelets Revealed by k-Space Spectroscopy

Abstract: We show that two-photon absorption (TPA) is highly anisotropic in CdSe nanoplatelets, thus promoting them as a new class of directional two-photon absorbers with large cross sections. Comparing two-dimensional k-space spectroscopic measurements of the one-photon and two-photon excitation of an oriented monolayer of platelets, it is revealed that TPA into the continuum is a directional phenomenon. This is in contrast to one-photon absorption. The observed directional TPA is shown to be related to fundamental ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 33 publications
(63 reference statements)
0
40
0
Order By: Relevance
“…Particularly 2D semiconductors in the form of nanoplatelets and sheets [1][2][3][4][5][6] receive growing attention due to fast radiative lifetimes 7,8 related to strong exciton correlation and the giant oscillator strength effect 4,9,10 allowing high quantum yields, 11,12 promising lasing properties [13][14][15] and high two-photon absorption. [15][16][17] Furthermore, their directed emission 18 and polarization 19 and well-width dependent high dark-bright splitting 20,21 of 3-6 meV are of direct interest. High exciton binding energies (of >100 meV) have been predicted and measured, 4,14,22,23 confirming the presence of robust excitons even at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly 2D semiconductors in the form of nanoplatelets and sheets [1][2][3][4][5][6] receive growing attention due to fast radiative lifetimes 7,8 related to strong exciton correlation and the giant oscillator strength effect 4,9,10 allowing high quantum yields, 11,12 promising lasing properties [13][14][15] and high two-photon absorption. [15][16][17] Furthermore, their directed emission 18 and polarization 19 and well-width dependent high dark-bright splitting 20,21 of 3-6 meV are of direct interest. High exciton binding energies (of >100 meV) have been predicted and measured, 4,14,22,23 confirming the presence of robust excitons even at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, with respect to ZB NPLs, the quantum confinement direction is along [100], so the 1hh-1e exciton originates from the 4p (x,y),Se → 5s Cd transition, while the 1lh-1e exciton results from the 4p (x,y,z),Se → 5s Cd transition (Figure 5e). 59 As a result, the upward and downward tendencies of CD peaks are opposite between 1hh-1e and 1lh-1e transitions due to their different polarization transitions. Moreover, because the 1SO state has the same symmetry with the 1lh state, the 1SO-1e exciton would show the same transition polarization with 1lh-1e exciton (Figure 5e,f).…”
mentioning
confidence: 98%
“…To reveal the origin of heavy‐ and light‐holes in CdSe NPLs, the band structure in the vicinity of the Γ‐point of the Brillouin zone were simulated with mBJ (modified Beak–Johnson) approximation, which was more accurate than that with GGA+U approximation ( Figure a; Figures S4 and S5 in details in the Supporting Information) . It was found that the simulated band gap was close to the value of the experimental results, and the excitation modes of heavy‐ and light‐holes were clearly observed.…”
mentioning
confidence: 65%